2007
DOI: 10.1179/acb.2007.061
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Cetuximab in Combination With Irinotecan Compared With Current Care in Metastatic Colorectal Cancer After Failure on Irinotecan – A Belgian Analysis

Abstract: This analysis compared the cost-effectiveness in Belgium of cetuximab plus irinotecan with current current care in the treatment of epidermal growth factor receptor (EGFR)-expressing metastatic colorectal cancer (CRC) that has failed irinotecan-containing therapy. Treatment outcomes and medical resource use data for patients receiving cetuximab plus irinotecan from the BOND study were compared with those from a matched group of patients (current care) (n = 66). Two scenarios were considered in which cetuximab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…The regimens used in the FEEs reviewed were not supported by CTs in half the reports, leading to indirect estimates of the efficacy of treatments [39][40][41]44]. Despite the variety of methods, almost all studies found very high incremental cost-effectiveness ratios (ICERs), over the formal or informal thresholds mentioned by authors.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The regimens used in the FEEs reviewed were not supported by CTs in half the reports, leading to indirect estimates of the efficacy of treatments [39][40][41]44]. Despite the variety of methods, almost all studies found very high incremental cost-effectiveness ratios (ICERs), over the formal or informal thresholds mentioned by authors.…”
Section: Resultsmentioning
confidence: 90%
“…The results of FEEs on CX before and after the relationship with KRAS mutation status was found did not give markedly different ICERs. Only one article, published (before the discovery of KRAS) in a local journal without any disclosure of conflicts of interest, found second-line treatment with CX + IRI cost-effective in Belgium for a virtual subgroup of patients [40]. Although the referred CT [48] consisted of only one arm of patients receiving CX + IRI with regular controls every six weeks, two virtual groups of patients were designed in this FEE: the first discontinued CX at six weeks, the second at 12 weeks in case of no response at those time points.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, many groups have investigated the combination of cetuximab with other drugs to enhance therapeutic efficacy. 35,36 Interestingly, the effect of cetuximab can be enhanced in cells with high levels of EGFR ligands such as EREG and AREG. 3,5 However, the results from this study showed that many gastric cancer cells did not express EREG because of aberrant DNA methylation.…”
Section: Cytotoxicity Of Cetuximab Enhanced By 5-aza-cdr Induction Ofmentioning
confidence: 99%
“…4,10,11 Current U.S. and European guidelines recommend that all mCRC patients receive tumor KRAS testing before consideration of treatment with an EGFR inhibitor and state that patients with known KRAS mutations should not receive either cetuximab or panitumumab as there is very little chance of a clinical benefit and the exposure to toxicity and highcost of treatment cannot be justified. 1,2 Although some studies have examined the cost-effectiveness of cetuximab treatment, [12][13][14][15] limited data exist on the cost-effectiveness or the potential cost savings that might accrue from the use of KRAS testing. Our objective was to determine the cost-effectiveness of testing for KRAS mutations before administering cetuximab or panitumumab for patients with mCRC in the United States and Germany and to document the economic implications of KRAS testing.…”
Section: Introductionmentioning
confidence: 99%